Identifikasi Potensi Bahaya di Ruang Tunggu Penumpang Bus Trans Kota Batam - Adi Nugroho (Institut Transportasi dan Logistik Trisakti, 2021)
Bus stop is one of the facilities it must be used by users of trans batam service. All facilities are built to provide convenience and comfort for users who used these services. Unfortunately, the repair efforts still left unfinished homework. Starting from the shape and size of different dimensions of facilities, as well as conformity to the needs of service users to safety aspects it must be fulfilled by providers. Through observational studies (observations) and literature studies, this study seeks to identify potential hazards that may occur in existing facilities in the bus stop area. This study uses a random sampling technique to obtain actual data / information by focused on the location (passenger waiting room) which has access to stop routes from various routes in Batam City, starting from the Batam Center and Batu Aji areas. Data analysis uses descriptive qualitative techniques, and combines with failure mode effect analysis (FMEA) techniques to obtain priority information on potential hazards that may occur based on the consensus of several parties who have a relationship with the service. Based on the results of analysis that has been done, information on 10 priorities of the highest potential hazards that may occur and become a priority for immediate improvement